Integrating Preventive Cardiology into Routine Clinical Practice: Are We Doing Enough? - Akhtar, Khurram (Pakistan Armed Forces Medical Journal, 2026)
Cardiovascular disease is the most common cause of mortality in the world with almost 17.9 million deaths every year, most of which are preventable. Prevention cardiology includes lipidlowering treatment, hypertension management, diabetes management, smoking cessation, lifestyle change, and cardiac rehabilitation that are supported by strong evidence and endorsed by the American College of Cardiology/American Heart Association (ACC/AHA) and European Society of Cardiology (ESC) guidelines. 1,2 There is, however, an enduring, well-reported gap between what is recommended, and what patients get. Although numerous preventive frameworks are available, compliance is still suboptimal and the difference between evidencebased recommendations and real-life practice still cost lives. 3 South Asia bears a disproportionate share of this burden. South Asians experience coronary artery disease earlier frequently before age 50 with a more aggressive phenotype driven by insulin resistance, central obesity, elevated lipoprotein(a), and tobacco use. 4 In Pakistan, Tertiary cardiac centers receiving large numbers of patients with acute coronary syndrome (ACS) daily, proper preventive cardiology services are infrequent, cardiac rehabilitation enrolment is minimal, and post-discharge secondary prevention treatment is often discontinued after several months. The question this editorial poses is not rhetorical: are we doing enough? The answer, plainly is no.